2022
DOI: 10.3390/su14052493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Conventional and Sustainable Modifiers to Improve the Stiffness Behavior of Weak Sub-Grade Soil

Abstract: The paper focuses on the improvement of the clayey soil (A-6) with the locally available and cheap modifiers, in terms of stiffness behavior of the weak subgrade soil for flexible pavement. The modifiers used include lime (hydrated), marble waste and sand. The soil specimens underwent triaxial testing and Clegg impact testing. Triaxial testing involved the assessment of the resilient modulus (MR) and impact testing using the Clegg Impact Hammer. According to the study, lime proved to be the most influencing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In order to investigate the impact of repeated cyclic stress amplitude on the cyclic and post-cyclic behavior in more detail, the repeated cyclic stress amplitudes range from 0.124 kN to 0.25 kN. According to previous studies [42,43], the conclusion that the confining pressures of 50 kPa, 100 kPa, and 150 kPa can represent the actual confining pressures of traffic loading can be achieved. Moreover, in order to investigate the influence law of confining pressure on the cyclic and post-cyclic behavior in more detail, the maximum confining pressure is 300 kPa.…”
Section: Test Procedures and Experimental Schemementioning
confidence: 99%
“…In order to investigate the impact of repeated cyclic stress amplitude on the cyclic and post-cyclic behavior in more detail, the repeated cyclic stress amplitudes range from 0.124 kN to 0.25 kN. According to previous studies [42,43], the conclusion that the confining pressures of 50 kPa, 100 kPa, and 150 kPa can represent the actual confining pressures of traffic loading can be achieved. Moreover, in order to investigate the influence law of confining pressure on the cyclic and post-cyclic behavior in more detail, the maximum confining pressure is 300 kPa.…”
Section: Test Procedures and Experimental Schemementioning
confidence: 99%
“…Furthermore, in order to study the impact of repeated cyclic stress amplitude on the accumulative strain in more detail, the repeated cyclic stress amplitudes used in this paper were 0.124 kN, 0.15 kN, 0.17 kN, 0.19 kN, 0.22 kN, and 0.25 kN. Based on previous studies [38,41,43], a general conclusion that the confining pressures of 50 kPa, 100 kPa, and 150 kPa can represent the actual confining pressures of traffic loading has been accepted. Furthermore, in order to study the impact of confining pressure on the accumulative strain in more detail, the confining pressures used in this paper were 50 kPa, 100 kPa, 150 kPa, 200 kPa, 250 kPa, and 300 kPa.…”
Section: Specimen Preparation and Experimental Schemementioning
confidence: 99%
“…It was revealed that lime can improve the stiffness of the subgrade better than other modifiers. It was also concluded that optimum moisture content increases with an increasing lime percentage and decreases with increasing marble and sand percentages [30].…”
Section: Introductionmentioning
confidence: 99%